Detection of Inflammatory Sacroiliitis in Children With Magnetic Resonance Imaging: Is Gadolinium Contrast Enhancement Necessary?. Issue 8 (28th July 2015) - Weiss, Pamela F.; Xiao, Rui; Biko, David M.; Johnson, Ann M.; Chauvin, Nancy A.
<x xml:space="preserve">Abstract</x> Objective In adults, gadolinium contrast enhancement does not add incremental value to fluid‐sensitive sequences for evaluation of bone marrow edema. This study was undertaken to determine if magnetic resonance imaging (MRI) contrast is necessary to assess lesions consistent with inflammatory sacroiliitis in children. Methods Patients with clinically suspected or diagnosed juvenile spondyloarthritis (SpA) underwent pelvic MRI consisting of multiplanar fluid‐sensitive and postgadolinium T1‐weighted fat‐saturated sequences including dedicated sacral imaging. Three radiologists independently evaluated the fluid‐sensitive sequences, and later, the complete study (including postcontrast images). With postcontrast imaging as the reference standard, we calculated the test properties of fluid‐sensitive sequences for depiction of acute and chronic findings consistent with sacroiliitis. Results The 51 patients had a median age of 15 years, and 57% were male. Nineteen patients (22 joints) were diagnosed as having sacroiliitis based on postcontrast imaging, and none had synovitis in the absence of bone marrow edema. All 22 joints demonstrated bone marrow edema on both fluid‐sensitive and postgadolinium T1‐weighted fat‐saturated sequences. Eighteen percent of joints with sacroiliitis had capsulitis, which was observed on both noncontrast and postcontrast imaging. Fifty‐nine percent of joints with sacroiliitis had synovitis on postcontrast imaging. Sensitivity, specificity, positive predictive value, and negative predictive value of fluid‐sensitive sequences for the detection of acute inflammatory lesions consistent with sacroiliitis using postgadolinium imaging as the reference standard were excellent. Interrater reliability was substantial for all parameters. Conclusion Our findings indicate that fluid‐sensitive sequences are sufficient to detect acute and chronic lesions consistent with inflammatory sacroiliitis in children.